Ki67 index importance in patients with breast cancer - Bondar, O. (Journal of Education, Health and Sport, 2024)
Breast cancer oncosurgery in its therapeutic and diagnostic strategies largely bases upon a considerable spectrum of laboratory findings. In the following article is presented a deep analysis of the series of studies devoted to the importance of oncological markers in practice, the necessity in proliferative activity index of the tumor to be determined, the diagnostic value of Ki-67 marker expression level for solving such tasks as evaluation of malignancy, selection of the best treatment strategy, adjuvant or neoadjuvant therapy, as well as the medical intervention results evaluation. On the grounds of the results, conclusions regarding the importance of determining the Ki-67 marker expression level as a comprehensive part of breast cancer diagnostics, the choice of proper treatment strategy and estimation of the one were made.